Stability of Monolithic MOF Thin Films in Acidic and Alkaline Aqueous Media - Tawheed Hashem; Elvia P. Valadez Sanchez; Evgenia Bogdanova; Anna Ugodchikova; Alaa Mohamed; Matthias Schwotzer; Mohamed H. Alkordi; Christof Wöll (Membranes, 2021)
In the context of thin film nanotechnologies, metal-organic frameworks (MOFs) are currently intensively explored in the context of both, novel applications and as alternatives to existing materials. When it comes to applications under relatively harsh conditions, in several cases it has been noticed that the stability of MOF thin films deviates from the corresponding standard, powdery form of MOFs. Here, we subjected SURMOFs, surface-anchored MOF thin films, fabricated using layer-by layer methods, to a thorough characterization after exposure to different harsh aqueous environments. The stability of three prototypal SURMOFs, HKUST-1, ZIF-8, and UiO-66-NH2 was systematically investigated in acidic, neutral, and basic environments using X-ray diffraction and electron microscopy. While HKUST-1 films were rather unstable in aqueous media, ZIF-8 SURMOFs were preserved in alkaline environments when exposed for short periods of time, but in apparent contrast to results reported in the literature for the corresponding bulk powders- not stable in neutral and acidic environments. UiO-66-NH2 SURMOFs were found to be stable over a large window of pH values.